The rational optimist : how prosperity evolves - Ridley, Matt. (New York : Harper, 2010)
The'New York Times'-bestselling author of'Genome' and'The Red Queen' offers a provocative case for an economics of hope, arguing that the benefits of commerce, technology, innovation, and change--cultural evolution--will inevitably increase human prosperity.
Includes bibliographical references and index.
Keywords: Wealth; Practical reason; Optimism